Application of Artificial intelligence (AI) in Pharmaceutical Industry: In-Depth Review - Ray Das, Avishikta; Samanta, Rojalini; Mishra, Rakhi; Sahu, Archana; Sahoo, Subhashree; Gorain, Amrit (Journal of Neonatal Surgery, 2025)
AI technologies are changing the pharmacy industry which includes the various processes of drug research, development, formulation, safety surveillance, and compliance to standards of law and ethics. This article explains in detail AI's impact on the Pharmacy industry. It includes the application of ML, DL, NLP, and computer vision, AI technologies on the different phases of life cycle of a drug. In drug discovery, AI boosts the determination of possible compounds with predictive modeling, virtual screening, SAR, and even de novo drug design. AI also enables the repurposing of existing drugs and aids in early-stage toxicity prediction. In formulation development, AI enhances the selection of excipients, design of dosage, and prediction of stability to be more precise and economical towards achieving patient-centered therapies. AI powered pharmacovigilance technologies have improved the monitoring of ADRs through real-time analysis of EHRs data, social networks, and cases which increases patient safety and rational regulatory actions. AI also helps in the preparation and review of relevant papers, documentation, e-submission, and adhering to international standards in the case of regulatory affairs. The transformative impact of AI tools and technologies are on varied fields and industries. Though, the reasoning for slower integration across the board are ethical concerns, data privacy issues, high implementation costs, and even a lack of professionals who are trained in order to utilize AI’s capabilities. This review is aimed AI's utilization in creating unique treatment strategies, managing rare health conditions, AI-enhanced clinical trial design and execution, AI-assisted manufacturing processes, and analysing mental health disorders. Considering continuous innovations alongside regulation framework support, it's now clear that AI will drastically change pharmaceutical research and healthcare services on a global scale